Bridging green HRM and employee environmental behaviour: A multi-path mediation model with leadership contingencies - Kalangi, Meyti Hanna Ester; Kusmaningtyas, Amiartuti; Ardiana, I Dewa Ketut Raka (Edelweiss Applied Science and Technology, 2026)
This study contributes to GHRM literature through the development of a dual-path approach in analysing environmentally friendly behaviours from both the cognition and behaviour approaches. Underpinning Social Learning, Social Cognitive and Social Exchange theories, the study identifies the mediating mechanisms and servant leadership as a moderator. Data collected from 293 shipping employees in Surabaya, Indonesia using survey questionnaires were analysed using PLS-SEM. The results indicate that GHRM positively influences eco-friendly behaviours directly as well as indirectly through the two mediators. This study confirms that both environmental awareness and proactive pro-environmental performance contribute as complementary mechanisms for connecting GHRM to behaviours. Servant leadership is found to negatively moderate environmental awareness; this means the existence of a substitution mechanism in terms of leadership style and HRM. In addition, the findings highlight the importance of formal green HR practices in encouraging sustainable employee conduct within environmentally sensitive industries. This study brings some new contributions to the literature on the relationship between GHRM and eco-friendly behaviour.